Dietary ω-3 intake for the treatment of morning headache: A randomized controlled trial - Marchetti, Marco; Gualtieri, Paola; De Lorenzo, Antonino; Trombetta, Domenico; Smeriglio, Antonella; Ingegneri, Mariarosaria; Cianci, Rossella; Frank, Giulia; Schifano, Giulia; Bigioni, Giulia; Di Renzo, Laura (Frontiers in Neurology, 2022)
Morning headache (MH) is a frequent condition with a not fully explained pathogenesis. During the past years, several studies have been performed to identify a better diet therapy to reduce the frequency and intensity of headaches. Our study aims to determine if an adequate omega-3 (ω-3) intake in a Modified Mediterranean Diet (MMD) can improve the frequency and intensity of MH and, subsequently, the quality of life. Of the 150 enrolled subjects, 95 met the inclusion criteria (63.3%). Patients were included in the study and randomized into two groups: group A following MMD A and group B following MMD B. The MMD A group was designed to arise at least a 1.5:1 ω-6/ω-3 ratio; the MMD B group was designed to derive at least a 4:1 ω-6/ω-3 ratio. Eighty-four subjects completed the 6 weeks intervention (56%). After 6 weeks (t1), group A showed a significant reduction in both Headache Impact Test-6 and Visual Analog Scale scores (p < 0.001, p < 0.001, respectively). During dietary treatment, group A progressively dismissed ketoprofen-based pharmacological treatment (p = 0.002) from baseline to t1. Furthermore, a decrease in the platelet-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio at t1 in group A (p = 0.02) was observed compared to group B. Concluding, this study provides evidence of a positive impact of ω-3-enriched MMD regimen on the inflammatory status and MH. Clinical trial registration:https://clinicaltrials.gov/ct2/show/NCT01890070, identifier: NCT01890070.